Study of electronic and magnetic properties in 4f electron based cubic EuAlO3: a first-principles calculation. (21st May 2015) - Sandeep,; Rai, D P; Shankar, A; Ghimire, M P; Khenata, R; Thapa, R K
Abstract: The electronic and magnetic properties of EuAlO3 are calculated by first-principles full-potential linearized augmented plane wave (FP-LAPW) method based on density functional theory (DFT). The exchange and correlation potential is treated with different approximations: mBJ and GGA + U . Coulomb repulsion ( U ) has been calculated using super-cell calculations for EuAlO3 . The GGA + U calculations reveal an indirect band gap of 4.6 eV for EuAlO3 in the spin down channel supporting the half metallic (HM) nature of the system. An effective integral magnetic moment also supported the HM nature of EuAlO3 .